USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI ERA DIGITAL ABAD 21: Usaha Mikro, Kecil Dan Menengah (Umkm) Era Digital Di Abad Ke-21 - Lily Zahra Firdausya; Dicky Perwira Ompusunggu (TALI JAGAD JOURNAL, 2023)
Micro, Small and Medium Enterprises (MSMEs) are an important sector in a country's economy. In the digital era of the 21st century, MSMEs face new challenges in utilizing digital technology in developing their businesses. This research aims to explore how MSMEs can take advantage of digital technology in the 21st century digital era. The method used is qualitative research by conducting an in-depth literature study on SMEs that have used digital technology in their business. The results of the study show that the use of digital technology can help MSMEs to increase operational efficiency, reach a wider market, and increase customer satisfaction. However, there are still obstacles such as limited access and skills in using digital technology that need to be overcome. Therefore, the government and related organizations need to provide the necessary support and training to MSMEs so that they can optimally utilize digital technology.